PENGARUH WORK-LIFE BALANCE DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT CARSOME ALAM SUTERA KOTA TANGERANG SELATAN - Wulan Dwi Putri; Agrasadya Agrasadya (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of work-life balance and workload on employee job satisfaction at PT Carsome Alam Sutera, South Tangerang City, both partially and simultaneously. The research method used is quantitative with a saturated sampling technique, so the entire population of 50 employees was taken as the sample. Data analysis was conducted through validity and reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results show that work-life balance has a positive and significant effect on job satisfaction. The simple regression equation obtained is Ỹ = 11.744 + 0.621X₁. The t-test result shows t-count (5.186) > t-table (2.010), thus hypothesis H1 is accepted. The correlation coefficient (r = 0.599) indicates a moderate relationship, with a determination coefficient of 35.9%. This means that better work-life balance increases employee job satisfaction. Furthermore, workload also has a positive and significant effect on job satisfaction. The simple regression equation obtained is Ỹ = 15.996 + 0.579X₂. The t-test result shows t-count (4.436) > t-table (2.010), thus hypothesis H2 is accepted. The correlation coefficient (r = 0.539) indicates a moderate relationship, with a determination coefficient of 29.1%. This suggests that a well-managed workload can improve job satisfaction. Simultaneously, work-life balance and workload significantly affect job satisfaction, with the multiple regression equation Y = 6.476 + 0.451X₁ + 0.328X₂. The F-test result shows F-count (17.404) > F-table (3.20), thus hypothesis H3 is accepted. The combined contribution of both variables to job satisfaction is 42.5%, while the remaining 57.5% is influenced by other factors not examined in this study.